Comparative analysis of the National and Communal Irrigation Systems' Water Governance the Philippines case - Nguyen, Miriam R.; Rola, Agnes C.; Alcala-Hall, Rosalie; Lizada, Joy C.; Abansi, Corazon L.; David, Myra E. (2015)
Using Saleth and Dinar's water governance framework, the study characterized irrigators' associations and examined how they operate and how they are managed. A total of 128 association presidents were surveyed in ten provinces in the Philippines and were asked about their knowledge and perception on the organization, natural resource policies, and water status in the locality.

The National Irrigation Systems (NIS) still has a formal structure as influenced by the National Irrigation Administration (NIA), it is assuming the characteristics of the Communal Irrigation Systems (CIS) management because of the paradigm shift to participatory irrigation management. The CIS, on the other hand, may remain to be an informal organization that is mimicking the character of the NIS, or it may become more formal.

The irrigators' associations were guided by institutional processes in water pricing. They differed on the basis and the average amount charged, and on modes of collection. Pricing did not reflect the true value of water with amounts set arbitrarily, and collections aimed at partial or full cost recovery.

Water administration is concerned with governance of water organization, policy and decision making, functional capacity, and government's level of influence on the water organization.

Water managers of NIS and CIS had dissimilar perceptions on irrigation water quality and quantity. Water laws (surface water, forest and land use) were viewed to have moderate to very strong linkage. Water rights were perceived to be common or shared equally by community members. Arising mainly from water scheduling/distribution, conflicts were resolved within the association or at the barangay (village) government.
Keywords: National Irrigation System; Irrigation System